Video-EEG monitoring in diagnostics and treatment efficacy evaluation in newly-diagnosed generalized epilepsy in adults - A. B. Kozhokaru; V. A. Karlov; P. N. Vlasov; A. S. Orlova (Эпилепсия и пароксизмальные состояния, 2021)
Introduction. Video-electroencephalography (EEG) monitoring (VEEGM) is an indispensable functional method in epileptology. However, virtually no trials on assessing efficacy of antiepileptic drugs (AED) by using VEEGM are available.Objective: to improve efficacy of EEG-diagnostics and evaluate the epileptiform activity index (EAI) in newly-diagnosed idiopathic generalized epilepsy in adult patients receiving  alproic acid and levetiracetam.Material and methods. T here w ere e nrolled 130 p atients: 6 0 (46.2%) m ales a nd 7 0 (53.8%) f emales w ith n ewlydiagnosedidiopathic generalized epilepsy (IGE), aged 22.51±8.9 years. All patients underwent VEEGM with quantitative EAI analysis at baseline visit and 1 3, 6 and 12 months later after treatment. Each seizure episode developed during the VEEGM study were assessed for type, time of seizure onset, relation to wake-sleep cycle, duration, ictal EEG pattern followed by diagnosing epileptic syndrome. Valproic acid and levetiracetam were used for initial therapy in groups per 65 patients in each. Treatment efficacy was assessed using parameters such as retention on therapy, absence of seizures, decrease of seizure frequency by >50%, decrease of seizure frequency by <50% – insufficient efficacy.Results. It was found that seizures during baseline VEEGM were recorded in 43.1% (n=56) patients, who were assigned to group 1, whereas remaining 74 (56.9%) patients were assigned to group 2. EAI was significantly higher in patients with seizures recoded at baseline VEEGM, compared to those lacking seizure episodes during initial VEEGM (p<0,001), mean EAI was also higher in group I at second (p<0.001) and third (p<0.001) visits. EAI magnitude at 6 and 12 months of study became virtually comparable in all groups and did not depend on AED prescribed. Treatment efficacy was higher in patients with IGE, with no  eizures recorded during the initial VEEGM.Conclusion. Long-term VEEGM allows unbiased assessment of treatment dynamics based on EAI analysis. The first 6 months of initial treatment titration in represent most crucial period for patients with newly-diagnosed IGE.